Empowerment for individual agency: an analysis of international organizations' curriculum recommendations. (15th March 2019) - Zapp, Mike
ABSTRACT: Much recent research stresses the increasing relevance of international organisations (IOs) for national education policymaking. Yet, IOs' curriculum recommendations have remained largely out of scope, although they provide a forceful example of 'soft' governance. Based on a content analysis of 83 documents from 42 inter/-nongovernmental, global and regional organisations involved in international education networks between 1990 and 2015, this paper identifies an expansive field of IOs directing growing attention to such curricular issues as student needs, educational goals and content, as well as issues of teaching and learning. In line with much cross-national curriculum research, analysis provides evidence for the trend towards a global curriculum model stressing empowerment, individual agency and psychosocial development. The article argues that the strong focus on human capabilities and human capital in IOs' curriculum policies reflects wider cultural transformations in contemporary world society. The article concludes by arguing for an expanded analytical scope of IOs' educational work and a reconsideration of causal explanations in curriculum theories.